PENGARUH DARI MULUT KE MULUT DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PELANGGAN PT. TOKOPEDIA TOWER JAKARTA - Zaenal Arifin; Arry Dwi Syahputra (Jurnal Manajemen Bisnis Krisnadwipayana, 2023)
This research was conducted with the aim of knowing the effect of Word Of Mouth and Product Quality on Purchase Decisions at the Tokopedia Online Media Shop at PT. Tokopedia Tower Jakarta, South Jakarta. The sampling technique used is a random sampling system. The data used is primary data by distributing questionnaires to consumers of PT. Tokopedia Tower Jakarta as a respondent. The data analysis technique used is descriptive analysis, multiple linear regression analysis, coefficient of determination analysis, and correlation coefficient analysis. The results showed that: 1) The wordof mouth variable has a positive and significant influence in improving purchasing decisions, 2) The product quality variable has a positive and significant influence in improving purchase decisions, 3) The word of mouth and product quality variables have a positive and significant influence in improving purchase decisions.